2005
DOI: 10.1097/01.gim.0000170776.31248.75
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling and breast cancer care: What are the potential benefits and policy implications?

Abstract: Purpose: Gene expression profiling has been proposed as an alternative to clinical guidelines to identify high-risk patients for adjuvant chemotherapy. However, the outcomes associated with gene expression profiling are not clear, and guidelines for the appropriate use of genomic technologies have not been established. Methods: We developed a decision analytic model to evaluate the incremental cost and quality-adjusted life years of gene expression profiling versus NIH clinical guidelines in a hypothetical coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…These results were recently confirmed on a larger set of patients [33]. The study by Oestreicher et al led to similar conclusions and suggested that performing gene expression profiling to identify the high-risk breast cancer patients who are likely to benefit most from adjuvant chemotherapy may yield net cost savings of $2,882 per patient [34]. All these studies were based on retrospective data, and their authors pointed out that the evidence about the economic outcomes was not very solid, since cost-effectiveness is difficult to assess until the clinical relevance of genomic testing for treatment decision-making purposes is confirmed.…”
Section: Discussionsupporting
confidence: 68%
“…These results were recently confirmed on a larger set of patients [33]. The study by Oestreicher et al led to similar conclusions and suggested that performing gene expression profiling to identify the high-risk breast cancer patients who are likely to benefit most from adjuvant chemotherapy may yield net cost savings of $2,882 per patient [34]. All these studies were based on retrospective data, and their authors pointed out that the evidence about the economic outcomes was not very solid, since cost-effectiveness is difficult to assess until the clinical relevance of genomic testing for treatment decision-making purposes is confirmed.…”
Section: Discussionsupporting
confidence: 68%
“…116 Of the six studies assessing Oncotype DX, 74,111,115 two estimated that the test would dominate standard care strategies, with Oncotype DX found to produce a gain in QALYs and a reduction in costs. 112,113 Both of these studies were funded by the manufacturer.…”
Section: Cost-effectiveness Analyses Of Multiparameter Testingmentioning
confidence: 99%
“…74,113,115,116 Two studies 112,113 assessed populations that included only patients with lymph node-positive disease, both of which evaluated Oncotype DX. Four studies reported specific details of patients' level of lymph node involvement; 112,113,115,116 most restricted their populations to patients with low levels (1-3) of lymph node involvement, with only one study 111 including patients with higher (1-9) lymph node involvement.…”
Section: Cost-effectiveness Analyses Of Multiparameter Testingmentioning
confidence: 99%
See 2 more Smart Citations